Ius liberorum : droit ou privilège ? - Sabine Armani (Cahiers Mondes Anciens)
This paper gives a detailed analysis of every source related to ius liberorum in the whole Roman Empire (be it literary, legal, epigraphic or papyrological). After a brief reminder of the conditions in which the ius liberorum appeared and of the rights it entitled to, the epigraphic sources are widely discussed. They suggest that the majority of the beneficiaries in the pars occidentalis were freed slaves, especially women, while women were indeed the only ones to claim the benefit of this right in the Greek-speaking part of the Empire. Ultimately, the author considers debates between supporters of an automatic right (once reached a sufficient number of children) on the one hand, and on the other hand, proponents of an imperial grant, whose hypothesis is mainly based on literary evidence. The attention is thus drawn to the way that ius liberorum is expressed (with or without an indication of the number of children) and to its possible meanings.